2021
DOI: 10.1093/annweh/wxab016
|View full text |Cite
|
Sign up to set email alerts
|

Welding Fume Exposure and Health Risk Assessment in a Cohort of Apprentice Welders

Abstract: Welding fumes vary in composition depending on the materials and processes used, and while health outcomes in full-time welders have been widely studied, limited research on apprentices exists. Besides, few data are available for metals such as vanadium and antimony. This study aimed to look at individual metals present in welding fumes in the learning environment of apprentice welders. Forty-three welders and 41 controls were chosen from trade programmes at the Northern Alberta Institute of Technology. Ambien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…In this study, Fe was found to be the chief component (22.6%) in welding fume generated from welding process, which is consistent with the previous findings (Dueck et al 2021;Ellingsen et al 2006;Insley et al 2019;Hariri et al 2018). Fe oxide is considered with little likelihood of causing chronic lung disease after inhalation.…”
Section: Concentration Of Contaminantssupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, Fe was found to be the chief component (22.6%) in welding fume generated from welding process, which is consistent with the previous findings (Dueck et al 2021;Ellingsen et al 2006;Insley et al 2019;Hariri et al 2018). Fe oxide is considered with little likelihood of causing chronic lung disease after inhalation.…”
Section: Concentration Of Contaminantssupporting
confidence: 91%
“…Flynn and Susi (2010) examined three databases suggesting that arc welding produces Mn exposures that are frequently close to or in excess of ACGIH TLV. Dueck et al (2021) conducted health risk assessment for twelve metals in a cohort of apprentice welders. Their findings showed that 8-hour TWA of Mn was in excess of ACGIH TLV for welding participants for day 50, which indicating that welder apprentices were at risk for overexposure to Mn.…”
Section: Exposure Concentration Calculation Resultsmentioning
confidence: 99%
“…It is believed that the presence of these contents has negative effects on the environment, particularly human health. Welders over a long period can have over exposure to manganese in their body or other elements, occupational asthma, and lung disorders [19,20]. Furthermore, the SMAW shows a better reduction of global warming than TIG through reducing CO2 emissions [21].…”
Section: Resultsmentioning
confidence: 99%
“…The fields around the welders (breathing zone) contain the contaminants produced during welding operations 21 . Lead is one of these pollutants, and 40% of inhaled lead is absorbed to blood circulation, which is the main rout of inorganic lead absorption 6,22 . in the present study, we have investigated the ALCs and BLCs of automobile welders in Birjand city.…”
Section: Discussionmentioning
confidence: 99%